Does a skier`s position on the ski affect the results of gliding tests used to assess ski-snow friction? - Federolf, P.; Rauscher, E.; Scheiber, P.; Schwameder, H. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
Ski manufacturers and ski racers test the gliding performance of skis by standardized gliding tests on straight runs. These test procedures have the advantage that they resemble the real situation in ski racing, but they have the disadvantage that the tester might influence the test result by influencing air drag or ski-snow friction. In this study we analysed if the position of the skier on the ski, which determines the force transfer from the skier onto the ski, affects the results of gliding tests. Three professional ski testers were asked to perform five different tasks: glide with the skis as flat as possible, stabilize your motion by edging the skis, glide in neutral, in forward, or in backward leaning position. The results show that edging on the one hand stabilizes the gliding motion, on the other hand, it significantly increases gliding time. The position of the skier in direction of the ski axis did not affect the skiers` gliding times, which contradicts a common opinion of many ski racing experts.